2022
DOI: 10.1177/00131245221076074
|View full text |Cite
|
Sign up to set email alerts
|

“Equity Work is Messy”: Exploring a Family and Community Partnership in One School District

Abstract: Focusing on family and community partnerships in schools is an important aspect to culturally responsive education, yet it is often an overlooked area. Educators must consider new models to engage community and family members to become partners in schools. This study presents finding from a mini-ethnographic case study and explores various stakeholders working as a collective to engage in culturally responsive work. In the model, group members interacted to develop curriculum proposals, professional developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The aforementioned claim corroborated Castillo's (2023) findings, which indicated that establishing community partnerships with educational institutions aided in the achievement of the organization's main goal. According to their supervisors' evaluations and their personal assessments, the instructors in this study viewed themselves as exceptionally skilled.…”
Section: Insights Of the Instructors' Proficiency Level In The Domain...supporting
confidence: 73%
“…The aforementioned claim corroborated Castillo's (2023) findings, which indicated that establishing community partnerships with educational institutions aided in the achievement of the organization's main goal. According to their supervisors' evaluations and their personal assessments, the instructors in this study viewed themselves as exceptionally skilled.…”
Section: Insights Of the Instructors' Proficiency Level In The Domain...supporting
confidence: 73%
“…Aspiring teacher educators require a framework for questioning power, diversity, and equity to ensure their students are not harmed by their practice (Atwater et al, 2014). Negative perceptions about students from traditionally marginalized backgrounds and their academic abilities are pervasive in the U.S., and a focus on culturally responsive 51 practice that rejects the deficit perspective allows educators to connect with their students and family (Castillo, 2023). Culturally responsive practice is a framework that recognizes cultural differences in students and family, and views diversity as an asset (Castillo, 2023).…”
Section: Community Engagement Through Collaboration and Mission Align...mentioning
confidence: 99%
“…Negative perceptions about students from traditionally marginalized backgrounds and their academic abilities are pervasive in the U.S., and a focus on culturally responsive 51 practice that rejects the deficit perspective allows educators to connect with their students and family (Castillo, 2023). Culturally responsive practice is a framework that recognizes cultural differences in students and family, and views diversity as an asset (Castillo, 2023). Castillo (2023) argued, "Teachers must help students to understand their own cultural beliefs and practices within the structure of a larger context," (p. 211).…”
Section: Community Engagement Through Collaboration and Mission Align...mentioning
confidence: 99%
See 1 more Smart Citation